MP-12 Effect of AKBISprob Supplementation on Antibacterial-Producing Lactic Acid Bacteria (LAB) Isolated from Laying Hens Intestine - . Nurliana; Sema Coumandary; Fashihah Rahmah Noya Farimansysh; . Sugito; Dian Masyitha; . Darmawi; . Erina; . Gholib; Erdiansya Rahmi; . Ismail (Hemera Zoa, 2018)
Generally, Bacteria in the intestine consist of beneficial bacteria and bacteria that have the potential to disrupt animal health such as pathogenic bacteria. The presence of pathogenic bacteria is one of the factors that cause gastrointestinal dysfunction, but can be suppressed by maintaining the presence of beneficial bacteria for the digestive tract, especially the type of Lactic Acid Bacteria (LAB) (Astuti, 2016). LAB has antagonistic activity because it is able to inhibit pathogenic bacteria so it can compete to maintain normal flora balance in the digestive tract.  The main inhibitory activity of LAB is caused by the accumulation of primary metabolites such as lactic acid, acetic acid, ethanol, and carbon dioxide. In addition, LAB is also capable of producing antibacterial compounds such as bacteriocins (Furtado et al., 2014). Naturally LAB has existed in the digestive tract of chickens, but it is easy to experience changes in the amount due to the influence of given the feed (Widodo et al., 2015). Feed and the environment can affect the composition of microbes in the digestive tract in chickens(Ghadban, 2002; Apajalahti et al., 2004). Provision of fermented feed can improve the composition of intestinal microflora and increase the number of LAB. Fermented feed is generally easily biodegradable and has a higher nutritional value than the original ingredient and it can reduce the pH of the digestive tract.AKBISprob is an alternative product to increase poultry production in the form of supplement made from a mixture of soybean wate, and palm kernel meal which is fermented with Aspergillus niger.  The fermentation process using Aspergillus niger can reduce the crude fiber contained in AKBIS, because the mold can produce amylase, pectinase, amyloglucosidase and cellulase enzymes which can degrade cellulose so that it is easier to digest. In addition, Aspergillus niger also produces metabolites in the form of citric acid which is a component that can reduce intestinal pH so that it is suitable for LAB growth. Based on research conducted by Nurliana et al. (2016; 2017), supplementation of 4% AKBISprob can maintain the chickens production and health as well increase the number of LAB and reduce the number of pathogenic bacteria such as Escherichia coli and Salmonella sp. in chickens intestine. Thus creating a balance of microflora in the digestive tract of laying hens. Based on the above reasons, it is necessary to conduct research on antibacterial detection of BAL in laying hens that have been given AKBISprob.